2018
DOI: 10.3390/resources7040064
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Big Data: Role in Smart Cities of India

Abstract: The intention of India’s Smart City Mission program is to achieve better living conditions in a sustainable environment with smart solutions. This program identifies the key challenges of urbanization and the environment. The mitigation of these challenges depends on the monitoring and assessment of multiple factors, including demography, education, health, and the environment; however, the inclusion of environmental factors are limited. The monitoring and assessment of environmental factors will continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 45 publications
(59 reference statements)
0
10
0
2
Order By: Relevance
“…Todas as UCs foram conectadas em razão das ligações entre UCs não possuírem ponderação de limite de distância para a dispersão de espécies, forçando dessa forma, a ligação entre elas. KUMAR, 2018). A rede ecológica urbana proposta neste estudo é uma solução baseada na natureza que pode proporcionar o aumento de fluxos biológicos na paisagem urbana, e consequentemente a manutenção ou a melhorias dos serviços ecossistêmicos prestados à população, além de proporcionar melhores experiências ao ar livre para a população urbana (METZGER, 2006;MELLO et al, 2020;WHEELER et al, 2020;XIE;BULKELEY, 2020).…”
Section: Resultsunclassified
“…Todas as UCs foram conectadas em razão das ligações entre UCs não possuírem ponderação de limite de distância para a dispersão de espécies, forçando dessa forma, a ligação entre elas. KUMAR, 2018). A rede ecológica urbana proposta neste estudo é uma solução baseada na natureza que pode proporcionar o aumento de fluxos biológicos na paisagem urbana, e consequentemente a manutenção ou a melhorias dos serviços ecossistêmicos prestados à população, além de proporcionar melhores experiências ao ar livre para a população urbana (METZGER, 2006;MELLO et al, 2020;WHEELER et al, 2020;XIE;BULKELEY, 2020).…”
Section: Resultsunclassified
“…Some studies focus on the importance of environment monitoring in smart cities [43]. For example Dwevedi et al [43] identified six environmental factors, such as landscape and geography, climate, atmospheric pollution, water resources, energy resources, and urban green spaces for Smart City Mission in India.…”
Section: Environmental Monitoringmentioning
confidence: 99%
“…Some studies focus on the importance of environment monitoring in smart cities [43]. For example Dwevedi et al [43] identified six environmental factors, such as landscape and geography, climate, atmospheric pollution, water resources, energy resources, and urban green spaces for Smart City Mission in India. These factors should be integrated in the development of smart cities and to be included in the monitoring system, which will be available through online platform to public to ensure that the society can participate in identifying the problems and offering help with the solutions.…”
Section: Environmental Monitoringmentioning
confidence: 99%
See 2 more Smart Citations